Smokers' behavioral intentions in response to a low-nicotine cigarette policy. (1st December 2019) - Patel, Minal; Cuccia, Alison F.; Czaplicki, Lauren; Donovan, Emily M.; Simard, Bethany; Pitzer, Lindsay; Hair, Elizabeth C.; Schillo, Barbara A.; Vallone, Donna M.
Highlights: Reducing cigarette nicotine may reduce use, yet population impact is unknown. Smokers' behavioral intentions in the event of a low-nicotine policy were measured. 78.4% would use low-nicotine cigarettes, 61.9% would quit, 46.5% would use e-cigs. Current users of e-cigarettes or CLCCs were more likely to use these products. Findings suggest reducing nicotine in all combustible tobacco products is needed. Abstract: Introduction: Evidence suggests that reducing the nicotine concentration in cigarettes to sub-addictive levels would reduce use. Until a low-nicotine cigarette policy is enacted, population-level effects are unknown. This study examines the behavioral intentions of current U.S. cigarette smokers if a low-nicotine policy were implemented. Methods: Data were drawn from a nationally representative probability-based panel and opt-in panel. Weighted logistic regressions examined likelihood to (1) smoke lower nicotine cigarettes, (2) quit using tobacco, (3) use e-cigarettes, (4) illegally buy high-nicotine cigarettes, and (5) smoke cigars, cigarillos, or little cigars (CLCCs) among smokers, controlling for demographics, tobacco products used, dependence, and intentions to quit cigarettes. Latent class analyses (LCA) characterized patterns of behavioral intentions. Results: If a low-nicotine policy were implemented, most participants indicated a likelihood to smoke low-nicotine cigarettes (78.4%) or quit tobacco (61.9%), followed by use e-cigarettes (46.5%). Individuals with greater dependence had greater odds of intending to smoke low-nicotine cigarettes, use e-cigarettes, and illegally buy high-nicotine cigarettes. Current e-cigarette or CLCCs users had higher odds of intending to use these products. LCA revealed that individuals would 1) use low-nicotine cigarettes with low intentions to use other tobacco products or 2) use multiple tobacco products, including low-nicotine cigarettes. Conclusions: A reduced nicotine standard for all combustible tobacco products is needed given that many tobacco users would likely intend to continue to use tobacco products. Differences in intentions by tobacco use and demographic characteristics indicate a need for additional cessation support and education around the harms of continued use of combustible tobacco.